강성분포의 변화가 초대형 부유식 구조물의 유탄성응답에 미치는 영향 고찰 - 김병완(Byoung-Wan Kim); 경조현(Jo-Hyun Kyoung); 홍사영(Sa-Young Hong); 조석규(Seok-Kyu Cho) (大韓造船學會 論文集, 2005)
Influences of stiffness distributions on hydroelastic responses of very large floating structures (VLFS) are studied in this paper. Hydroelastic responses are calculated by direct method employing higher-order boundary element method (HOBEM) for fluid analysis and finite element method (FEM) for structure analysis. In structural analysis using FEM, Mindlin plate elements are used. An 1 km-long VLFS with uniform stiffness and modified VLFS with varying stiffness distributions are considered in numerical analysis. Responses of VLFS increase in flexible parts and decrease in stiff Parts. Reduction degree of displacements of VLFS with stiffened center is larger than that of VLFS with stiffened sides.